A Post Hoc Analysis on the Incidence of Congenital Heart Disease in Baku-Azerbaijan calculated by a Prospective Epidemiology Study - Petropoulos, Andreas (Journal of Humanitarian Cardiovascular Medicine, 2023)
Background: The incidence of Congenital Heart Disease (CHD)in Azerbaijan was firstly published following a prospective study, using Echo-2D as a study method, in 2019. Aim: Of this post hoc analysis of the first ever prospective epidemiology study that calculated incidence and types of CHD in Baku, Azerbaijan, is to verify the forms of diseases that will have and early clinical impact on the patients and the health system of the country. Population-method: From June 2016 to August 2018, 2570, term neonates were screened in 2 major state maternity hospitals in Baku. Their screening was randomized to equal females/males with not known previous obstetric alert regarding CHD. Scanning was done by two teams of pediatric cardiologists by using echo-2D. Each team was ‘blinded’ to the findings of each other. All scans were recorded, and a third senior physician reevaluated them. Results: From 2570 term neonates of the general population, they detected 47 CHD’s. From them, 17 were critical and severe-CHD and 7/47(14.9%) were of moderate complex. 17/47 (36.2%) were cyanotic and 30/47(63.8%) were non-cyanotic. The incidence of simple CHD was 25/47(53.2%). Analysis of the specific anatomy is presented in table1. The estimated incidence was 1.83%. As this incidence has been among the highest reported a post hoc analysis has clarified and presented an important clinical rate of 1.48% after redacting minimal defects without any clinical significance, as minor PDA’s, ASD II, VSD’s. A post hoc calculation of BAov, revealed an anatomical BAov incidence of 1.65% and a functional BAov incidence of 1.4%. Conclusions: This first-ever prospective epidemiology study in Azerbaijan involving a cohort equal to 1.65% of the annual living births of the country, estimated a high incidence of CHD. This is among the highest reported globally. The amount of critical and severe CHD after the post hoc analysis increased from 46.8% to 55.3%. The incidence of cyanotic CHD after the post hoc analysis increased from 36.2% to 42.1%. These high numbers are possibly related to an isolated population and conjugated marriage customs of the country. As this represented a state population health burden a post hoc analysis based on clinical important CHD minimized the calculated index nearby 20%.